Feeding Sensitivity at 3-Months Predicts Parental Feeding Style at 3-Years - Worobey, John (International Journal of Child Health and Nutrition, 2018)
Objective: To examine the association between maternal responsive feeding in infancy and later parental feeding style in childhood, with a secondary aim of linking parenting style to child weight status Design: Short-term, longitudinal study Subjects: 65 mother-infant pairs, followed from 3-months to 3-years Methods: Mother-child dyads were seen at enrollment, observed at home when the infant was 3-months-old, and at home again when the infant turned 2-years of age. When the child reached 3-years, mothers self-reported their feeding style. Results: Responsive maternal feeding at 3-months predicted an authoritative feeding style at 3-years, and the authoritative feeding style was associated with a healthier weight status. Conclusion: Responsive feeding in infancy may serve as the foundation for responsive feeding in childhood and may serve to help in reducing obesity risk